Answer:
a. 0.55
b. 0.68
c. 0.18
Step-by-step explanation:
a. The probability that E2 does not occur is one minus the probability that E2 occurs:
[tex]1-P(E2)= 1- 0.45\\1-P(E2) = 0.55[/tex]
b. The probability that either E1 or E2 occurs is given by the sum of their individual probabilities minus their joint probability:
[tex]P(E1\ or\ E2) = P(E1)+P(E2)-P(E1, E2)\\P(E1\ or\ E2)=0.37+0.45-0.14\\P(E1\ or\ E2)=0.68[/tex]
c. The probability that neither E1 nor E2 occurs is one minus the probability of E1 occurring minus the probability of E2 occurring:
[tex]1-P(E1)-P(E2)= 1- 0.37 -0.45\\1-P(E1)-P(E2) = 0.18[/tex]